Contribution of specific gray matter volumes to insomnia severity: Developing topics. (7th December 2020) - Martínez, Neus Falgàs; Allen, Isabel Elaine; Mumford, Paige S; Essanaa, Youssef M; Le, Michelle M; You, Michelle; Grinberg, Lea Tenenholz; Neylan, Thomas; Rosen, Howard J; Kramer, Joel H; Walsh, Christine M
Abstract: Background: There is an increasing awareness that sleep disturbances are a risk factor for dementia (Sindi, 2018). Prior case‐control studies have suggested that certain alterations in brain structure could be associated with insomnia status (Sexton, 2014; Grau‐Rivera, 2019). Specifically, they mainly described smaller cortical volumes in orbitofrontal and cingulate areas. However, it remains unclear whether there is a gradient association between these regions and the severity of insomnia. Therefore, our goal was to investigate the association between gray matter (GM) and white matter (WM) regions with insomnia severity. We hypothesized that a smaller orbitofrontal and cingulate cortex is associated with greater insomnia severity. Method: 122 healthy subjects (age 74.7±5.7 years old, 55.7% female) were recruited from the Healthy Aging Study at Memory and Aging Center, UCSF. All participants were determined to be cognitively healthy following a neurological evaluation, neuropsychological assessment and informant interview. Participants had a 3T brain MRI and completed the Insomnia Severity Index (ISI), a subjective measure of insomnia (Bastien, 2001). FreeSurfer was used to obtain GM and WM volumes. We used linear regression models to evaluate the relevance of regional GM and WM volumes to ISI, controlling for age and total intracranial volume. Result: Distribution of ISI scores ranged from 0 to 16 (4.8±4.2). Regression models showed that smaller pars orbitalis (β=‐0.29, p =0.008), supramarginal (β=‐0.26, p =0.019), transverse temporal (β=‐0.24, p =0.018), postcentral (β=‐0.24, p =0.027), rostral anterior cingulate (β=‐0.23, p =0.044) and isthmus cingulate (β=‐0.23, p =0.045) GM regions were associated with higher ISI scores. White matter regions were not associated with ISI. Conclusion: Lower volumes in certain cortical regions contributed to a higher degree of perceived insomnia severity. Conversely, white matter regions had no effect. Our results not only reinforce the involvement of orbitofrontal and cingulate regions with the presence of insomnia (Sexton, 2014; Grau‐Rivera, 2019) but furthermore, extend this showing that insomnia severity is associated with volumetric values in these areas. Further studies are needed to clarify how these insomnia‐related brain changes in healthy subjects align with an increased risk of dementia.